A reduced reference video quality assessment of H.264 and mpeg2 codec based on sharpness metric. Issue 11 (5th January 2017) - Ben Amor, Mohamed; Larabi, Mohamed‐Chaker; Kammoun, Fahmi; Masmoudi, Nouri
Abstract: In this paper, we propose a new perceptually significant video quality metric for the H.264/Motion Picture Expert Group (MPEG)‐4 Advanced Video Coding (AVC) and MPEG2 standard. Our method operates in the spatial domain by using the Sobel filter. The proposed approach does not require a high computational complexity and can be suitable for real‐time evaluation. We evaluate the performance of the proposed method by using three Common Intermediate Format sequences at different compression rates. The comparison of the obtained results is made with some video quality models using "LIVE", "IVP" and "IRCCyN/IVC 1080i" databases. The performance metrics, i.e. Pearson and Spearman correlation coefficients, indicate that the proposed method gives a good performance in H264 and MPEG2 codec distortions with the three databases comparing with other models. Abstract : We propose a new perceptually significant video quality metric for the H.264/ Motion Picture Expert Group (MPEG‐4) Advanced Video Coding (AVC) and MPEG2 standard. Our method operates in the spatial domain by using the Sobel filter. The proposed approach does not require a high computational complexity and can be suitable for real‐time evaluation.